0
$\begingroup$

Let $f : \mathbb{S}^3 \to \mathbb{S}^2$ be the map

$$ f(z_1,z_2) = (2z_1 \overline{z_2}, \vert z_1 \vert^2 - \vert z_2 \vert^2), $$

where we regard $\mathbb{S}^3 \subset \mathbb{C}^2$ and $\mathbb{S}^2 \subset \mathbb{C} \times \mathbb{R}$. In the 3-sphere we have the following equivalence relation: $(z_1,z_2) \sim (w_1,w_2)$ iff there exists $\lambda \in \mathbb{S}^1$ such that $z_i = \lambda w_i$, $i=1,2$. I want to show that $z \sim w$ iff $f(z) = f(w)$, so that $f$ induces an injective continuous function $\overline{f} : \mathbb{C}\mathbb{P}^1 \to \mathbb{S}^2$. I already showed that if $z \sim w$, then $f(z) = f(w)$ (this is straightforward). How do I prove the converse?

$\endgroup$
  • 1
    $\begingroup$ Perhaps you should also mention that we regard $S^2 \subset \mathbb{C} \times \mathbb{R}$. $\endgroup$ – Paul Frost Aug 27 '18 at 7:29
0
$\begingroup$

We have $(z_1,z_2) \in S^3$ if and only if $\lvert z_1 \rvert^2 + \lvert z_2 \rvert^2 = 1$. Hence $f(z_1,z_2) = f(w_1,w_2)$ implies $2 \lvert z_1 \rvert^2 - 1 = \lvert z_1 \rvert^2 - \lvert z_2 \rvert^2 = \lvert w_1 \rvert^2 - \lvert w_2 \rvert^2 = 2 \lvert w_1 \rvert^2 - 1$ and therefore $\lvert z_1 \rvert = \lvert w_1 \rvert$. We conclude that $z_1 = \lambda w_1$ where $\lambda = z_1/w_1 \in S^1$. But now $2\lambda w_1 \overline{z_2} = 2 z_1 \overline{z_2} = 2 w_1 \overline{w_2}$, hence $\lambda \overline{z_2} = \overline{w_2}$ and therefore $z_2 = \lambda \overline{\lambda } z_2 = \lambda \overline{\lambda \overline{z_2}} = \lambda \overline{\overline{w_2}} = \lambda w_2$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.